2012
DOI: 10.1002/ajmg.b.32032
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide supported psychosis risk variant in ZNF804A gene and impact on cortico–limbic WM integrity in schizophrenia

Abstract: Genome-wide association, case association genetic and meta-analytic studies have highlighted ZNF804A as a robust genome-wide supported susceptibility gene for schizophrenia (SCZ). In view of the possible involvement of ZNF804A gene in early neurodevelopment and cellular processes including oligodendrocyte proliferation and differentiation, we examined the effect of ZNF804A on brain WM (WM) integrity in patients with SCZ. Based on extant data in healthy controls (HC), we hypothesized that ZNF804A risk variant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 50 publications
(65 reference statements)
5
29
0
Order By: Relevance
“…ZNF804A polymorphisms appears to be linked to abnormal brain structure and function in many mental illnesses (Bergmann et al, 2013;Donohoe et al, 2011;Esslinger et al, 2009;Guella et al, 2014;Kuswanto et al, 2012;Lencz et al, 2010;Mohnke et al, 2013;Rasetti et al, 2011;Schultz et al, 2014;Wassink et al, 2012;Wei et al, 2013). The rs1344706 SNP alters the thickness and functional connectivity of several regions, such as the prefrontal cortex, that comprise the default mode network (DMN; Schultz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZNF804A polymorphisms appears to be linked to abnormal brain structure and function in many mental illnesses (Bergmann et al, 2013;Donohoe et al, 2011;Esslinger et al, 2009;Guella et al, 2014;Kuswanto et al, 2012;Lencz et al, 2010;Mohnke et al, 2013;Rasetti et al, 2011;Schultz et al, 2014;Wassink et al, 2012;Wei et al, 2013). The rs1344706 SNP alters the thickness and functional connectivity of several regions, such as the prefrontal cortex, that comprise the default mode network (DMN; Schultz et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of the risk T-allele also exhibited higher WM density in the bilateral hippocampus in schizophrenia patients compared with non-risk allele carriers (Wei et al, 2013). However, another study reported that schizophrenia patients who were TT carriers had lower fractional anisotropy (i.e., a measure that correlates with fiber integrity) in the parietal lobes, left cingulate gyrus, and other corticolimbic brain regions (Kuswanto et al, 2012). Additionally, some studies provided negative results with regard to the effect of rs1344706 on WM tract integrity (Wei et al, 2013).…”
Section: Genetic Associationmentioning
confidence: 97%
“…Walter et al [52] show decreased activity in frontal and parietal cortical regions and aberrant connectivity between these regions during a theory of mind task in healthy risk allele carriers. A diffusion tensor imaging study reports lower fractional anisotropy (a measure correlated with fiber integrity) in parietal lobes and left cingulate gyrus in schizophrenia patients homozygous for the risk allele [53]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, changes in WM integrity may be a fundamental pathophysiological mechanism underlying the clinical presentation of schizophrenia, present before the appearance of clinical symptoms. There are several studies supporting this hypothesis, proposing the change in WM as an endophenotypical feature of the disease (Davis et al, 2003;Camchong, 2009;Abdul-Rahman et al, 2011;Kunimatsu et al, 2012;Kuswanto et al, 2012;Scheel et al, 2012). Together, the data to date strongly suggests that there is an underlying abnormality in the WM tracts of patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 90%